Efficacy of sirolimus in blue rubber bleb nevus syndrome. - Mouhsine, Z.; El Fatoiki , F.E.; Hali, F.; Chiheb, S. (European Journal of Pediatric Dermatology, 2024)
“Blue rubber bleb nevus syndrome” (BRBNS) is a rare vascular condition characterized by multifocal venous malformations, affecting various organs, but primarily the skin and gastrointestinal tract. Sirolimus promotes the regression of skin lesions and is well tolerated, although further studies are needed to evaluate long-term efficacy and safety. We describe the case of a 16-year-old girl affected by exclusively cutaneous BRBNS since the age of 11, who was treated with sirolimus and benefited from it.